Edukasi Perbankan Syariah dan Literasi Digital Bagi Siswa/i SMK Swasta Budi Agung Medan - Putri Nazli; Nur Anzelina Hrp; Bima Anugrah (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
The rapid development of digital technology requires young generations to possess adequate digital and financial literacy, including an understanding of Islamic banking systems. However, the level of Islamic banking literacy and the use of digital financial services among vocational high school students remains relatively low. This community service activity aims to enhance students' understanding of basic Islamic banking concepts and improve digital literacy in utilizing digital-based financial services safely and wisely. The methods used include counseling, interactive lectures, discussions, and hands-on practice with digital banking platforms. The results indicate an increase in students' knowledge of Islamic banking principles, such as the prohibition of usury (riba), profit-sharing mechanisms, and basic use of digital financial services. This activity is expected to foster financially and digitally competent students who can act as educational agents in their communities.